B 3a + 2b = c formülünde çözün. A.b = -3a + c B.b = c-2 / 3a C.b = -3a + c / 2 D.b = 2c / 3a

B 3a + 2b = c formülünde çözün. A.b = -3a + c B.b = c-2 / 3a C.b = -3a + c / 2 D.b = 2c / 3a
Anonim

Cevap:

# B = C / 2-3 / 2a #

Açıklama:

Çıkarma #3 A#:

# 2b = C-3a #

bölerek #2#

# B = C / 2-3 / 2a #

Cevap:

# B = (C-3a) / 2to (b) #

Açıklama:

# "3a" 'yı her iki taraftan da çıkararak "2b" yi izole et "#

#cancel (3a) iptal (3a) + 2b = C-3a #

# 2b = C-3a #

# "iki tarafı da 2'ye böl" #

# (iptal et (2) b) / iptal (2) = (c-3a) / 2 #

# B = (C-3a) / 2 = (- 3a + c) '/ 2to (b)' #